Minutes of the ultimate meeting of this International Editorial Board of the Metalurgija Journal 2025 y - Mamuzić Ilija (Metalurgija)
Minutes of the Last Meeting of the Editorial Board of the Journal Metalurgija. The Croatian Metallurgical Society will enter liquidation in 2025 and will cease to be the publisher of the journal Metalurgija. Consequently, the current Editorial Board and its membership will also cease to function.